Early changes in cardiovascular structure and function in adolescents with type 1 diabetes. Issue 1 (December 2016) - Bradley, Timothy; Slorach, Cameron; Mahmud, Farid; Dunger, David; Deanfield, John; Deda, Livia; Elia, Yesmino; Har, Ronnie; Hui, Wei; Moineddin, Rahim; Reich, Heather; Scholey, James; et al.
Abstract Background Children with type 1 diabetes (T1D) are at higher risk of early adult-onset cardiovascular disease. We assessed cardiovascular structure and function in adolescents with T1D compared with healthy controls and the relationships between peripheral vascular function and myocardial parameters. Methods and results 199 T1D [14.4 ± 1.6 years, diabetes duration 6.2 (2.0–12.8) years] and 178 controls (14.4 ± 2.1 years) completed endothelial function by flow mediated vasodilatation (FMD), arterial stiffness using pulse wave velocity (PWV) along with M-mode, pulse wave and tissue Doppler, and myocardial deformation echocardiographic imaging. Systolic (113 ± 10 vs. 110 ± 9 mmHg; p = 0.0005) and diastolic (62 ± 7 vs. 58 ± 7 mmHg; p < 0.0001) blood pressures, carotid femoral PWV and endothelial dysfunction measurements were increased in T1D compared with controls. Systolic and diastolic left ventricular dimensions and function by M-mode and pulse wave Doppler assessment were not significantly different. Mitral valve lateral e' (17.6 ± 2.6 vs. 18.6 ± 2.6 cm/s; p < 0.001) and a' (5.4 ± 1.1 vs. 5.9 ± 1.1 cm/s; p < 0.001) myocardial velocities were decreased and E/e' (7.3 ± 1.2 vs. 6.7 ± 1.3; p = 0.0003) increased in T1D. Left ventricular mid circumferential strain (−20.4 ± 2.3 vs. −19.5 ± 1.7 %; p < 0.001) was higher, whereas global longitudinal strain was lower (−19.0 ± 1.9 vs. −19.8 ± 1.5 % p < 0.001) in T1D. Conclusions Adolescents with T1D exhibit early changes in blood pressure, peripheral vascular function and left ventricular myocardial deformation indices with a shift from longitudinal to circumferential shortening. Longitudinal follow-up of these changes in ongoing prospective trials may allow detection of those most at risk for cardiovascular abnormalities including hypertension that could preferentially benefit from early therapeutic interventions.